Computational Methods in Multiphase Flow V 2009
DOI: 10.2495/mpf090361
|View full text |Cite
|
Sign up to set email alerts
|

CFD simulation with multiphase flows in porous media and open mineral storage pile

Abstract: In open storage piles in bulk solids port terminals, power stations and cement factories, not only the solid and porous barrier behaviour in front of the pile is important, but also the effect that porous and solid barriers produce when they are behind the pile.Considering the dust propagation behind the pile, the solid barriers are more effective than the porous ones. But, the effect of the porous barriers on the wind velocity distribution, mainly in zones between the barriers and the piles should be taken in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…When modelling a 37° angle cone, it is observed that the recovery zone of the wind flow velocity is smaller, 9H becoming 8H. The choice of these slope angles is based on former research by TORAÑO et al [12], TORAÑO et al [7], TORNO et al [5], TORNO [3] and DIEGO et al [8], in which they determined that for the use of standard EPA emission formulas [29], a 0.2 relation between the radio and the pile height was necessary. This relation has been used by STUNDER and ARYA [20] which is the same as the one used in our studies, (11 m high and 37° angle).…”
Section: Wind Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…When modelling a 37° angle cone, it is observed that the recovery zone of the wind flow velocity is smaller, 9H becoming 8H. The choice of these slope angles is based on former research by TORAÑO et al [12], TORAÑO et al [7], TORNO et al [5], TORNO [3] and DIEGO et al [8], in which they determined that for the use of standard EPA emission formulas [29], a 0.2 relation between the radio and the pile height was necessary. This relation has been used by STUNDER and ARYA [20] which is the same as the one used in our studies, (11 m high and 37° angle).…”
Section: Wind Resultsmentioning
confidence: 96%
“…For each type of fence, solid fence (ε=0%), porous fence (ε=30%) and no fence (ε=100%), 183 wind velocity measurements with hot-wire anemometer and 60 dust concentration measurements, measuring Total Particle and PM10, were developed. Some turbulence models used by the authors in other studies [5,[7][8]12] were included again in these simulations, carried out by 3D CFD (Computational Fluid Dynamics) code ANSYS CFX-10.0 [18−19]. These simulations were validated by the measurement programmes mentioned above, determining that the vortex, which is produced between the fence and the pile, diminishes its velocity when a solid fence is changed for a porous fence (ε=30%).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the effect of the porous barriers at 30% adjacent to the pile has been studied, achieving an emission reduction produced to windward of pile due to the solid barrier effect over the wind flow (Torno et al [7]). …”
Section: Introductionmentioning
confidence: 99%